Plataforma hardware in the loop para teste de leis de controle de voo e desenvolvimento de unidade de navegação inercial - Silva, Willian Rigon (2018)
The work presents a Hardware in The Loop (HIL) system design and construction, aimed to test automatic flight control laws with the X-Plane flight simulator. In addition, the development, integration, and tests of an Inertial Navigation System (AHRS/INS - Attitude and Heading Reference System/Inertial Navigation System) is presented. The plant used in the study is the Unmanned Aerial Vehicle (UAV) Half Scale (HS) of the Hórus Squadron, of the Brazilian Air Force (FAB). The designed HIL system can be used to test the implementation of the control laws in the flight computer, controlling the UAV model in the X-Plane. The HIL test permits a quicker and safer automatic flight control law development. To show the HIL system capabilities, results for several control laws are presented: Fly-By-Wire, Altitude Hold Autopilot, and Mach Hold Autopilot. The UAV analytical model was constructed using the classic longitudinal flight dynamics equations, with stability and control derivatives given by USAF DATCOM. The control laws were designed with the classical control theory, using the linearized model for the cruise flight phase. The longitudinal flight modes were compared between the analytical model and the X-Plane model. With the objective to implement the flight control laws in the real UAV, an inertial navigation system was developed (AHRS/INS). The objective of the AHRS/INS system is to deliver the necessary flight information to the control system. Static tests of the AHRS/INS system are shown, also it is presented a methodology to calibrate magnetometers installed in aircraft. Concluding, proposal for future works and HIL and AHRS/INS systems optimizations are presented.